Inclusive Leadership and Employees’ Helping Behaviors: Role of Psychological Factors - Qasim, Samina; Usman, Muhammad; Ghani, Usman; Khan, Kalimullah (Frontiers in Psychology, 2022)
Based on social learning theory, the present study investigates the relationship between inclusive leadership and employees helping behaviors. Further, psychological mechanisms (psychological safety and psychological engagement) are investigated in the relationship between inclusive leadership and employees' helping behaviors. The data was collected in three time-lags through a questionnaire from 409 nurses working in the health sector of Pakistan. The collected data was analyzed through IBM-SPSS and AMOS to test the proposed model. The study's findings show that inclusive leadership positively influences employees helping behaviors. Moreover, psychological safety and engagement mediate the relationship between inclusive leadership and employee helping behaviors. Theoretical and practical implications for managers, practitioners, and organizations are discussed, while study limitations and directions for future research are also highlighted.